DAMPAK PERKAWINAN SIRI TERHADAP HAK WARIS ISTRI DAN ANAK - Deviani Theresia Br Barus; Fitria Agustin (CV. Denasya Smart Publisher, 2026)
Siri marriage is a type of marriage performed in accordance with religious law but not officially registered by the government. This can give rise to legal issues, particularly regarding inheritance rights for the wife and children. This study aims to examine the legal position of wives and children from siri marriages in obtaining inheritance rights, both under Islamic law and Indonesian law. It also investigates the impact of the lack of marriage registration on proving inheritance rights. The methodology used is normative legal research, with a regulatory and conceptual approach through a literature review. The results of this study indicate that under Islamic law, wives and children in siri marriages still have the right to inheritance, but their position under positive law is weakened by the lack of administrative evidence such as a marriage certificate. Therefore, they need to undergo additional legal processes such as marriage confirmation and proof of civil relationship before they can obtain inheritance rights. Therefore, marriage registration is crucial to provide initial legal protection to ensure legal certainty and avoid future inheritance disputes.